The effects of internal branding and brand commitment on employee brand performance: an empirical evidence from Pakistan’s public sector banks - Muhammad, Shoaib (2021)
Many public sector firms have embraced branding to promote the firm's desired image. However, the application of internal branding in public sector enterprises is relatively a newer topic for researchers and practitioners. While public sector branding has grown in prominence, employee branding has garnered less attention. The study examines the impact of internal branding practices on employee brand performance and brand commitment's mediating role in this relationship. The effect of internal branding on employee brand performance is explored theoretically and tested empirically in the Pakistani banking sector. Social Exchange Theory served as the study's foundation. The research paradigm is positivism, so a quantitative approach is used in which questionnaires were distributed to managerial and non-managerial staff. Multi-stage sampling was employed, whereby purposive and stratified random sampling with equal distribution were used. A questionnaire survey was conducted, and 426 responses were found to be valid. Statistical analyses were performed using the SmartPLS 3.2.9 version. The results show that brand knowledge and internal brand communication & training affect employee brand performance positively and significantly. However, brand performance is not influenced by brand identification and brand trust. Besides, brand commitment mediated all the relationships. As this research's sample is limited to public banks, the study should be replicated in other types of banks and countries to ensure the generalizability of the identified relationships. By conducting an empirical analysis of the effects of internal branding from employees' perspectives, these findings contribute to earlier research. Furthermore, the study advances the internal branding and employee brand performance research streams, which have previously been under-explored in the banking context. Managers, particularly those in the service industry, should ensure that adequate brand management processes are in place to support staff brand performance. The study concludes with a discussion, implications, limitations, and future research directions.